School pressure and psychosomatic complaints among Swedish adolescents: does physical activity play a buffering role? - Birgersson, Alicia; Landberg, Jonas; Låftman, Sara Brolin (Frontiers in Public Health, 2024)
Background: School pressure is a significant stressor in the lives of adolescents, recognised to be associated with psychosomatic complaints. Therefore, the exploration of potential buffering factors is a relevant task. This study aimed to examine the association between school pressure and psychosomatic complaints and the potentially moderating role of physical activity in a Swedish national sample of adolescents.: Data were derived from the 2017/2018 Swedish Health Behaviour in School-aged Children (HBSC) survey, involving 3,745 participants aged 11-15 years. School pressure and physical activity were measured using single items. Psychosomatic complaints were assessed through an additive index based on the frequency of eight complaints. Covariates included gender, grade, and family affluence.Results: Linear regression analyses demonstrated a positive graded association between school pressure and psychosomatic complaints, while an inversely graded association was observed between physical activity and psychosomatic complaints. Physical activity did, however, not moderate the link between school pressure and psychosomatic complaints.Even though physical activity did not serve as a buffer, the direct effects of school pressure and physical activity on psychosomatic complaints suggest that supporting young people in managing school demands and promoting their engagement in physical activities could be effective measures in alleviating psychosomatic complaints.